Dakwah Persuasif pada Media Instagram: Telaah Kajian Tokoh Hawaariyyun - Mukarramah, Niatul; Madya, Efi Brata (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
Instagram has become a strategic platform for preachers to reach a wider audience. One of the da’wah influencers on Instagram media is @Hawaariyyun, he is famous for his preaching content in spreading Islam on Instagram social media. However, during competition, da’wah needs to be packaged persuasively to attract attention and interest and be accepted by the audience. This article analyzes the persuasive da’wah strategy used by the Instagram account @Hawaariyyun using four methods: Association, Integration, Pay-off, and Icing. This research aims to identify and implement these methods in the content of da’wah and their influence on mad’u. This research shows that Hawaariyyun effectively uses this method to build emotional connections, increase credibility, and motivate the audience to accept the da’wah message.